Framing Analysis of Mirna’s Father in the Documentary Film “Ice Cold: Murder, Coffee, and Jessica Wongso” - Persada, Muhammad Rizqi; Fajrini, Nurkhalila (Jurnal Komunikasi dan Bisnis, 2024)
Documentary films serve as powerful media for conveying messages and stories to audiences. Netflix released a documentary titled "Ice Cold: Murder, Coffee, and Jessica Wongso", which gained widespread attention by highlighting the cyanide coffee murder case involving Jessica Wongso and Mirna Salihin—an incident that became national news. This study focuses on analyzing the framing of Edi Darmawan, the father of the late Mirna, portrayed as an arrogant and ambitious figure in the film. The research employs a qualitative approach, using the framing analysis model developed by Zhongdang Pan and Gerald M. Kosicki. The findings reveal that Edi is framed as a person with strong ambitions and arrogance in his pursuit of justice for his daughter, resulting in negative public perceptions. This study provides insights into how visual media, especially documentary films, shape public perceptions regarding complex legal and social issues. Furthermore, the results highlight the role of visual narratives in influencing audience attitudes and encourage critical reflection on the way stories are framed within visual media.